Preparation of controlled gold nanoparticle aggregates using a dendronization strategy - Paez, Julieta Irene (2012)
In this work, a dendronization strategy was used to control interparticle spacing and the optical properties of gold nanoparticle (NP) aggregates in aqueous media. To achieve this goal, two dendritic disulfides bearing different functionalities on their periphery were synthesized and used as ligands to dendronize gold NPs. The dendronized NPs then undergo aggregation; this process was followed by UV–vis spectroscopy, dynamic light scattering (DLS), and transmission electronic microscopy (TEM) measurements and correlated with Generalized Mie Theory electrodynamics calculations. For comparison, NP functionalization was also studied using a nondendritic ligand. It was found that the use of dendritic disulfides allows for the preparation of controlled NP aggregates. This study demonstrates how different dendronization parameters, such as disulfide concentration, temperature, time and nature of the ligand (dendritic vs nondendritic), determine the control exerted over the size and stability of the NP aggregates.